KAiKU Music Glove transforms music education : exploring new and novel music technologies in the music classroom - Danso, Andrew (2019)
The concept of using one's hand to learn music dates back over 1000 years to The Guidonian hand, which used the palm and fingers to indicate note names. The Guidonian method was effective in teaching musical structures and is one of the primary concepts behind KAiKU Music Glove. KAiKU Music Glove is a wearable device designed for music education. This thesis explores how iPad and KAiKU Music Glove technology affect academic performance in elementary school children by testing both technologies in the music classroom. The study gathers attitudinal responses, a test of knowledge and includes qualitative observations of students using the technology. The study was conducted in an elementary classroom with two classes. Motivation levels to use the two technologies scored high in both classes, showing non-significance when compared with one another. The hypothesis that KAiKU Music Glove users will respond higher in motivation than iPad users is not supported. Ease of use response levels scored high in both classes showing non-significance when compared with one another. The hypothesis that KAiKU Music Glove users will respond with higher variance than iPad users in ease of use is not supported. The students viewed the technologies as musical instruments similarly with non-significance reported, however a close to significant result is registered, suggesting a distinction in how the technologies appeared to the students periodically during the study. Qualitative findings suggest technical problems experienced by KAiKU Music Glove users influenced how the technology appeared to the students. Overall, iPad scored comparatively higher in total attitudinal response and registered a 2% margin of improvement in the test of knowledge compared to KAiKU Music Glove. This confirms iPad to affect academic performance in elementary school children with greater magnitude than KAiKU Music Glove. KAiKU Music Glove's promising performance indicate it is achieving the balance in learning and innovation many educational technologies strive for.